PELATIHAN PELAPORAN AKUNTANSI PADA UMKM CV. CITRA ABADI BATU - Sri Wahjuni Latifah; Ahmad Waluya Jati; Agustin Dwi Haryanti (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat, 2021)
Ipteks for the community on the CV.Agro Citra Abadi Batu with the aim of helping partners in order to have a reliable accounting information systems that can provide important information, accurate and timely, so that owners and parties concerned can analyze and take the right decision. Problems of the partners is not yet able to evaluate his performance for not having a system of accounting information to make financial statements.          The purpose of this activity is to improve the understanding and knowledge of human resources. The lasting company has to information system of accounting and financial reporting. Besides helping partners in designing the accounting  system in accordance with the conditions of the partners.          Method to  solving the problem: advising system of accounting information based SAK EMKM, discussing, accounting software design,and implementation of accounting software.The results of these activities shows that there is an increased understanding and ability of partners in the field of accounting. Partners can understand and apply the concept of entity references  separation of business transactions with private transactions. Proven partners may draw up financial statements, can use the financial statements as the basis for evaluation of performance and can use for materials management decision-making